Analysis of Ireland’s Economic Policy Response to the 2008 Global Financial Crisis and Its Impact on the National Economy - Mufida Fisca Salsabilla; Siti Nur Aisyah; Suci Irianti; Nurzalina Nurzalina (Austronesia Akademika, 2026)
This study analyses Ireland’s economic policy response to the 2008 Global Financial Crisis and its impact on the national economy. The crisis revealed deep structural vulnerabilities within Ireland’s pre-crisis growth model, particularly excessive credit expansion, property-market dependence, weak financial regulation, and high banking-sector exposure to real estate. Using a qualitative descriptive-analytical literature review based exclusively on secondary data, this study examines peer-reviewed articles, official policy documents, EU–IMF reports, government publications, and relevant economic datasets. The findings show that Ireland’s initial response focused on banking-sector stabilisation through the blanket bank guarantee, bank recapitalisation, and the establishment of the National Asset Management Agency. These policies prevented immediate financial collapse but transferred substantial private banking risks into public liabilities, contributing to rising sovereign debt and fiscal pressure. Subsequent fiscal consolidation and austerity measures helped restore market credibility and supported Ireland’s return to international financial markets, yet they also generated significant social costs, including pressure on households, public services, employment, and vulnerable groups. The study further finds that Ireland’s recovery was supported by export-led growth, foreign direct investment, institutional reform, and improved financial regulation. However, the recovery remained uneven, as macroeconomic improvement did not fully eliminate social hardship, housing pressures, and structural dependence on external investment. The study concludes that Ireland’s experience offers an important lesson in crisis governance: financial stabilisation must be accompanied by social resilience, institutional accountability, and balanced long-term economic reform.